Analisis Privasi dan Kepercayaan Terhadap Keamanan Data Pengguna Aplikasi On Demand Service Menggunakan Metodologi Structural Equation Modeling - Raka Kurnia Novriantama; Ari Kusyanti; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
On Demand Service is a location-based app on smartphones that utilize user data in their operations. On Demand Service users need to share digital information in order to use the available features, but there is no guarantee of security on the matter. It is not known what factors affect the nature of a user in sharing a digital identity. This research is useful to know the factors that influence an individual in the desire to share digital identity on On Demand Service. This research model consists of 7 constructs. Habits, Benefit, Perceived Privacy Risks, Trust, Perceived Control, Previous Experience dan Willingness to Share Digital Identities. In this study will use a model adapted from the research model Sanjib Tiwari and Koehorst. Models obtained from previous research and adapted for the model according to the study. The data analysis in this study comes from questionnaires distributed to On Demand Service users. Analysis using Structural Equation Modeling (SEM). The results show that the Habits, Benefit and Perceived Control variables are the reasons why people have a desire to share digital information on On Demand Service.